High-dielectric-constant high-resistance-value low-loss pulse power type capacitor and dielectric material and preparation process thereof

The dielectric material with specific doping and synthesis methods enhances the dielectric constant, resistance, and temperature stability of pulse power ceramic capacitors, addressing the limitations of existing technologies for high-energy applications.

CN119252661AActive Publication Date: 2025-01-03FUJIAN TORCH ELECTRON TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411323075.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-23
Publication Date
2025-01-03
Estimated Expiration
2044-09-23

AI Technical Summary

Technical Problem

Existing pulse power ceramic capacitors face challenges in achieving high dielectric constants, high resistance, and low loss while maintaining stability across varying temperatures, which are crucial for applications in new energy vehicles and other fields requiring high energy absorption and release in extreme conditions.

Method used

A dielectric material comprising (Sr0.7Ba0.3-xMg0.3-x)(Ti0.8Ru0.2-yTe0.2-y)O3 doped with La3(SbzCe1-z)Zr3O12, Ba(Zn1/6Nb1/3)(B2O4), MnCO3, MnO2, and Li2SiO3, synthesized through molten salt and solid phase methods, followed by an MLCC process with 70Ag-30Pd electrodes, to optimize polarization strength and reduce energy loss.

Benefits of technology

The resulting capacitor exhibits high dielectric constant, low dielectric loss, high resistance, and excellent bias characteristics, with improved temperature stability and discharge performance, suitable for high-energy applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a dielectric material for a high-dielectric constant, high-resistance and low-loss pulse power type capacitor and a preparation process, the dielectric material takes (Sr0.7 BaxMg (0.3-x) (Ti0. 8RuyTe0.2-y) O3 as a base material, and is added with the following components: La3 (SbzCe1-z) Zr3O12, Ba (Zn1 / 6Nb1 / 3) (B2O4) 2, MnCO3, MnO2 and Li2SiO3, x is more than 0 and less than 0.3, y is more than 0.1 and less than 0.2, and z is more than 0.7 and less than 1.0, Ru and Te elements are added in the process of manufacturing a main base material of the pulse power type ceramic dielectric material provided by the invention to prepare (Sr0.7 BaxMg (0.3-x) (Ti0. La3 (SbzCe1-z) Zr3O12 and Ba (Zn1 / 6Nb1 / 3) (B2O4) 2 synthesized by a solid phase method are added, and the prepared dielectric material has excellent electrical properties of high dielectric constant, high resistance and low loss in the presence of a trace Li element by adjusting the proportion of Mn < 2 + > / Mn < 4 + >, and a capacitor made of the dielectric material has excellent bias characteristic, stable charge and discharge performance and relatively large discharge current, and can be applied to the field of capacitors. The ceramic capacitor is suitable for pulse power type ceramic capacitors.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of ceramic capacitor preparation, and specifically relates to a dielectric material and a preparation process for a high-dielectric-constant, high-resistance, low-loss pulse power capacitor. Background Art

[0002] Pulse energy storage dielectric materials can store high-density charges in a short period of time, and release energy in the form of pulses to generate extremely high currents. Among them, pulse power ceramic capacitors have good temperature characteristics, high withstand voltage, good insulation performance, moisture and heat resistance, low dielectric loss, stable high and low temperature pulse discharge characteristics, and extremely high charge and discharge life. They are widely used in new energy vehicles, laser weapons, electromagnetic catapults and other fields. In recent years, with the rapid development of new energy vehicles, the proportion of pulse power ceramic capacitors in the spare parts of new energy vehicles has gradually increased. Electric vehicles need to absorb or release a large amount of energy in a short period of time in conditions such as overtaking and braking kinetic energy recovery, ultra-high power charging and discharging. Pulse power ceramic capacitors, as key components in new energy vehicles, play a key role in the above conditions. Electric vehicles need to work in low temperatures in winter and high temperatures in summer, which puts higher requirements on the temperature stability of capacitors. With the development of electric vehicles towards electronics, intelligence, and informatization, the requirements of high capacitance and miniaturization are put forward. Therefore, the development of pulse power dielectric materials with higher dielectric constants and more stable performance can adapt to the development trend of electronics, intelligence, and informatization technology. . Summary of the invention

[0003] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a high dielectric constant, high resistance, low loss pulse power capacitor and its dielectric material and preparation process.

[0004] The present invention adopts the following technical solution: A dielectric material for high dielectric constant, high resistance and low loss power capacitor, with 100 mole parts of (Sr 0.7 Ba x Mg 0.3-x )(Ti 0.8 Ru y Te 0.2-y )O3 as the base material, and the following components are added in molar proportions: 2 to 10 parts of La3(Sb z Ce 1-z )Zr3O 12 , 1~3 parts of Ba(Zn 1 / 6 Nb 1 / 3)(B2O4)2, 0.5~1 parts of MnCO3, 0.2~0.5 parts of MnO2, 0.1~0.2 parts of Li2SiO3, wherein 0<x<0.3, 0.1<y<0.2, 0.7<z<1.0.

[0005] Furthermore, the Ba(Zn 1 / 6 Nb 1 / 3 )(B2O4)2 is synthesized from BaCO3, ZnO, Nb2O5 and B2O3 using a fixed method.

[0006] Furthermore, the (Sr 0.7 Ba x Mg 0.3-x )(Ti 0.8 Ru y Te 0.2-y )O3 is (Sr 0.7 Ba 0.27 Mg 0.03 )(Ti 0.8 Ru 0.15 Te 0.05 )O3.

[0007] Furthermore, the La3(Sb z Ce 1-z )Zr3O 12 La3(Sb 0.87 Ce 0.13 )Zr3O 12 .

[0008] A process for preparing a dielectric material for a high dielectric constant, high resistance and low loss power capacitor comprises the following steps: Step 1: Preparation by molten salt method (Sr 0.7 Ba x Mg 0.3-x )(Ti 0.8 Ru y Te 0.2-y )O3; Step 2: Solid phase method to prepare La3(Sb z Ce 1-z )Zr3O 12 ; Step 3: Solid phase method to prepare Ba(Zn 1 / 6 Nb 1 / 3 )(B2O4)2; Step 4: (Sr 0.7 Ba x Mg 0.3-x )(Ti 0.8 Ru y Te 0.2-y)O3、La3(Sb z Ce 1-z )Zr3O 12 、MnCO3、MnO2、Ba(Zn 1 / 6 Nb 1 / 3 )(B2O4)2, Li2SiO3, add deionized water and zirconium oxide beads, ball mill for 4 to 6 hours, then dry and crush to obtain the dielectric material for high dielectric constant, high resistance and low loss pulse power ceramic capacitor.

[0009] Further, step one specifically comprises: weighing SrCO3, BaCO3, MgO, TiO2, RuO2, TeO2, NaCl, and KCl in a molar ratio of 0.7:x:(0.3-x):0.8:y:(0.2-y):(2~4):(2~4), respectively, adding anhydrous ethanol and zirconium oxide beads, mixing and ball milling for 6~8h, drying and calcining the powder at a temperature of 800~900°C for 2-3h, and naturally cooling to room temperature; the calcined product is ultrasonically cleaned with deionized water, washed and filtered for multiple times until there is no Cl - After washing and drying, (Sr 0.7 Ba x Mg 0.3-x )(Ti 0.8 Ru y Te 0.2-y )O3.

[0010] Furthermore, step 2 specifically includes: La3(Sb z Ce 1-z )Zr3O 12 The specific preparation process is as follows: La2O3, Sb2O3, Ce2O3, and ZrO2 are weighed separately in a molar ratio of 1.5:z / 2:(1-z) / 2:3, deionized water and zirconium oxide beads are added, mixed and ball-milled for 4-6 hours, and the powder is dried and calcined at 1200-1300°C for 1-3 hours, and naturally cooled to room temperature to obtain La3(Sb z Ce 1-z )Zr3O 12 .

[0011] Further, step three specifically includes: Ba(Zn 1 / 6 Nb 1 / 3 The specific preparation process of )(B2O4)2 is as follows: BaCO3, ZnO, Nb2O5, and B2O3 are weighed in a molar ratio of 1:1 / 6:1 / 6:3, and appropriate amounts of deionized water and zirconium oxide beads are added and mixed and ball-milled for 4-6 hours. After drying, the powder is transferred to a temperature of 600-800°C and calcined for 1-3 hours, and naturally cooled to room temperature to obtain Ba(Zn 1 / 6Nb 1 / 3 )(B2O4)2.

[0012] A high dielectric constant, high resistance and low loss power capacitor is prepared by using the above dielectric material.

[0013] A preparation process for a high dielectric constant, high resistance and low loss power capacitor comprises the following steps: subjecting the dielectric material to an MLCC process, using 70Ag-30Pd as an inner electrode, sintering in an air atmosphere at a temperature of 1000-1200°C, and keeping the temperature for 2-5 hours to obtain the pulse power capacitor.

[0014] It can be seen from the above description of the present invention that, compared with the prior art, the present invention has the following beneficial effects: First, the dielectric material for pulse power ceramic capacitors proposed in the present invention combines the advantages of high dielectric constant and high withstand voltage of SrTiO3 and BaTiO3, and introduces Mg, Ru and Te elements by molten salt method to achieve double element co-doping of A / B positions uniformly to make a composite structure (Sr 0.7 Ba x Mg 0.3-x )(Ti 0.8 Ru y Te 0.2-y )O3, and use it as the main substrate, doped with La3(Sb z Ce 1-z )Zr3O 12 , forming a uniform perovskite structure, and by regulating the doping of Mn 2+ / Mn 4+ The ratio of Zn to Ba(Zn) was used to optimize the polarization strength of the ceramic material and to synthesize the improved sintering aid Ba(Zn 1 / 6 Nb 1 / 3 )(B2O4)2 is used to lower the firing temperature, and a trace amount of Li2SiO3 is added to reduce energy loss, so that the obtained dielectric material has high density, large dielectric constant, low dielectric loss, high resistance, and excellent bias characteristics, making it suitable for use as a pulse power ceramic capacitor.

[0015] Second, La3(Sb z Ce 1-z )Zr3O 12 Lanthanum zirconate and cerium zirconate have the advantages of good high temperature stability and high radiation impedance, but the thermal conductivity of lanthanum zirconate is low and the resistance to temperature shock is poor. It needs to be doped with cerium zirconate with high thermal conductivity and low thermal expansion coefficient, and under the promotion of a small amount of Sb2O3, La3(Sb z Ce 1-z )Zr3O 12It shows good resistance to temperature shock. However, too much cerium zirconate will cause the porcelain to absorb too much heat and reduce the resistance. Therefore, cerium zirconate is doped into lanthanum zirconate. By adjusting La3(Sb z Ce 1-z )Zr3O 12 The ratio of Sb and Ce in the ceramic ensures that the dielectric material can maintain the stability of the ceramic body when facing temperature shock.

[0016] Third, by regulating Mn 2+ / Mn 4+ The ratio of Mn to the A / B position of the main substrate is precisely controlled. The different doping amounts of Mn elements have a large difference in the potential difference generated at the A / B position, making it easier to polarize under the action of an external electric field, resulting in a higher polarization strength. P m .

[0017] Fourth, directly adding Nb2O5 can greatly reduce the dielectric loss of the dielectric material, but at the same time it will cause the dielectric constant of the dielectric material to decrease significantly. If the sintering aid BaZnB2O4 is combined with Nb2O5 to form a ternary central ring structure of Ba-Nb-Zn, the excessive aggregation of grains will be prevented during the sintering process, thereby preventing the disordered growth of large grains. The grains of the ceramic will grow in an orderly manner during the sintering process, and the entropy of the system will be reduced, thereby reducing the sintering temperature, improving the density of the porcelain body, and then improving the puncture strength of the porcelain body.

[0018] Fifth, lithium plays a key role in the field of energy storage materials. Adding lithium to dielectric materials can P m When the external electric field is lost, the residual polarization intensity P r The curve shifts rightward, closer to P m curve, reducing energy loss, thereby retaining more energy for release during discharge. In particular, if there is an excess of lithium, after a certain number of times of charge and discharge of the capacitor, lithium dendrites will grow at the boundaries of the inner electrodes, resulting in a significant reduction in the breakdown strength of the porcelain body and causing capacitor failure. Therefore, the amount of lithium added must be controlled particularly accurately. DETAILED DESCRIPTION

[0019] The present invention is further described below through specific implementation modes.

[0020] A high dielectric constant, high resistance and low loss pulse power ceramic capacitor is prepared by dielectric material. The preparation process comprises the following steps: subjecting the dielectric material to an MLCC process, using 70Ag-30Pd as an inner electrode, sintering in an air atmosphere at a temperature of 1000-1200°C, and keeping the temperature for 2-5 hours to obtain a pulse power ceramic capacitor.

[0021] Dielectric material, with 100 mol parts of (Sr 0.7 Ba x Mg 0.3-x )(Ti 0.8 Ru y Te 0.2-y )O3 as the base material, and the following components are added in molar proportions: 2 to 10 parts of La3(Sb z Ce 1-z )Zr3O 12 , 1~3 parts of Ba(Zn 1 / 6 Nb 1 / 3 )(B2O4)2, 0.5~1 parts of MnCO3, 0.2~0.5 parts of MnO2, 0.1~0.2 parts of Li2SiO3, wherein 0<x<0.3, 0.1<y<0.2, 0.7<z<1.0.

[0022] Among them, Ba(Zn 1 / 6 Nb 1 / 3 )(B2O4)2 is synthesized from BaCO3, ZnO, Nb2O5 and B2O3 using a fixed method.

[0023] (Sr 0.7 Ba x Mg 0.3-x )(Ti 0.8 Ru y Te 0.2-y )O3 is (Sr 0.7 Ba 0.27 Mg 0.03 )(Ti 0.8 Ru 0.15 Te 0.05 )O3.

[0024] La3(Sb z Ce 1-z )Zr3O 12 La3(Sb 0.87 Ce 0.13 )Zr3O 12 .

[0025] The preparation process of the dielectric material comprises the following steps: Step 1: Preparation by molten salt method (Sr 0.7 Ba xMg 0.3-x )(Ti 0.8 Ru y Te 0.2-y )O3: 0.7 in molar ratio: x: (0.3-x): 0.8: y: (0.2-y): (2~4): (2~4) Weigh SrCO3, BaCO3, MgO, TiO2, RuO2, TeO2, NaCl, KCl respectively, add anhydrous ethanol and zirconium oxide beads, mix and ball mill for 6~8h, dry the powder and calcine it at 800~900℃ for 2-3h, and cool it naturally to room temperature; the calcined product is ultrasonically cleaned with deionized water, washed and filtered several times until there is no Cl - After washing and drying, (Sr 0.7 Ba x Mg 0.3-x )(Ti 0.8 Ru y Te 0.2-y )O3; Step 2: Solid phase method to prepare La3(Sb z Ce 1-z )Zr3O 12 : La2O3, Sb2O3, Ce2O3, and ZrO2 were weighed separately in a molar ratio of 1.5: z / 2: (1-z) / 2: 3, deionized water and zirconium oxide beads were added, mixed and ball-milled for 4-6 hours, and the powder was dried and calcined at 1200-1300°C for 1-3 hours, and naturally cooled to room temperature to obtain La3(Sb z Ce 1-z )Zr3O 12 ; Step 3: Solid phase method to prepare Ba(Zn 1 / 6 Nb 1 / 3 )(B2O4)2: BaCO3, ZnO, Nb2O5, B2O3 were weighed in a molar ratio of 1:1 / 6:1 / 6:3, and appropriate amount of deionized water and zirconium oxide beads were added and mixed and ball-milled for 4-8 hours. After drying, the powder was transferred to calcination at 600-800℃ for 1-3 hours and naturally cooled to room temperature to obtain Ba(Zn 1 / 6 Nb 1 / 3 )(B2O4)2; Step 4: Prepare the (Sr 0.7 Ba x Mg 0.3-x )(Ti 0.8 Ru y Te 0.2-y )O3、La3(Sb z Ce 1-z )Zr3O 12、MnCO3、MnO2、Ba(Zn 1 / 6Nb 1 / 3 )(B2O4)2, Li2SiO3, add deionized water and zirconium oxide beads, ball mill for 4 to 6 hours, then dry and crush to obtain the dielectric material for the high dielectric constant pulse power ceramic capacitor.

[0026] Example 1 A high dielectric constant, high resistance and low loss pulse power ceramic capacitor is prepared using dielectric material. Its preparation process includes the following steps: subjecting the dielectric material to an MLCC process, using 70Ag-30Pd as an inner electrode, sintering in an air atmosphere at a temperature of 1100°C and keeping warm for 3 hours to obtain a pulse power ceramic capacitor.

[0027] Dielectric material, with 100 mol parts of (Sr 0.7 Ba 0.27 Mg 0.03 )(Ti 0.8 Ru 0.15 Te 0.05 )O3 as the base material, and the following components were added in molar proportions: 7 parts of La3(Sb 0.87 Ce 0.13 )Zr3O 12 , 1 part of Ba(Zn 1 / 6 Nb 1 / 3 )(B2O4)2, 0.7 parts of MnCO3, 0.35 parts of MnO2, 0.12 parts of Li2SiO3.

[0028] The preparation process comprises the following steps: Step 1: Preparation by molten salt method (Sr 0.7 Ba 0.27 Mg 0.03 )(Ti 0.8 Ru 0.15 Te 0.05 )O3: molar ratio of 0.7: 0.27: 0.03: 0.8: 0.15: 0.05: (2~4): (2~4) Weigh SrCO3, BaCO3, MgO, TiO2, RuO2, TeO2, NaCl, KCl respectively, add anhydrous ethanol and zirconium oxide beads, mix and ball mill for 6 hours, dry the powder and calcine it at 800~900℃ for 2.5 hours, and cool it naturally to room temperature; the calcined product is ultrasonically cleaned with deionized water, washed and filtered several times until there is no Cl - After washing and drying, (Sr 0.7 Ba 0.27 Mg 0.03 )(Ti 0.8 Ru 0.15 Te0.05 )O3; Step 2: Solid phase method to prepare La3(Sb 0.87 Ce 0.13 )Zr3O 12 : La2O3, Sb2O3, Ce2O3, and ZrO2 were weighed in a molar ratio of 1.5:0.435:0.065:3, deionized water and zirconium oxide beads were added, mixed and ball-milled for 5 hours, and the powder was dried and calcined at 1280°C for 2.5 hours, and naturally cooled to room temperature to obtain La3(Sb 0.87 Ce 0.13 )Zr3O 12 ; Step 3: Solid phase method to prepare Ba(Zn 1 / 6 Nb 1 / 3 )(B2O4)2: BaCO3, ZnO, Nb2O5, B2O3 were weighed in a molar ratio of 1:1 / 6:1 / 6:3, and appropriate amount of deionized water and zirconium oxide beads were added and mixed and ball-milled for 5 hours. After drying, the powder was transferred to calcination at 720℃ for 2.5 hours and naturally cooled to room temperature to obtain Ba(Zn 1 / 6 Nb 1 / 3 )(B2O4)2; Step 4: (Sr 0.7 Ba 0.27 Mg 0.03 )(Ti 0.8 Ru 0.15 Te 0.05 )O3、La3(Sb 0.87 Ce 0.13 )Zr3O 12 、Ba(Zn 1 / 6 Nb 1 / 3 )(B2O4)2, MnCO3, MnO2, Li2SiO3, add deionized water and zirconium oxide beads, ball mill for 6 hours and then dry and crush to obtain the dielectric material for the high dielectric constant pulse power ceramic capacitor.

[0029] The raw material composition and preparation process of Examples 2-5 are basically the same as those of Example 1, except that the ratios of the raw materials are different. The specific parameters are shown in Table 1.

[0030] The raw material composition and preparation process of Comparative Examples 1-5 are basically the same as those of Example 1, except that the raw material ratios are different. The specific parameters are shown in Table 1.

[0031] Table 1 Composition table (mol%) <![CDATA[(Sr 0.7 Consider 0.27 Mg 0.03 )(A 0.8 Ru 0.15 Eat 0.05 )O3]]> <![CDATA[La3(Sb 0.87 What 0.13 )Zr3O 12 ]]> <![CDATA[Ba(Zn 1 / 6 Nb 1 / 3 )(B2O4)2]]> <![CDATA[MnCO3]]> <![CDATA[MnO2]]> <![CDATA[Li2SiO3]]> Example 1 100 7 1 0.7 0.35 0.12 Example 2 100 10 1 0.7 0.35 0.12 Example 3 100 7 2.5 0.7 0.35 0.12 Example 4 100 7 1 0.35 0.35 0.12 Example 5 100 7 1 0.5 0.5 0.12 Comparative Example 1 100 0 1 0.7 0.35 0.12 Comparative Example 2 100 7 0 0.7 0.35 0.12 Comparative Example 3 100 7 1 0 0.35 0.12 Comparative Example 4 100 7 1 0.7 0 0.12 Comparative Example 5 100 7 1 0.7 0.35 0 Comparative Example 6 A high dielectric constant, high resistance and low loss pulse power ceramic capacitor is prepared using dielectric material. Its preparation process includes the following steps: subjecting the dielectric material to an MLCC process, using 70Ag-30Pd as an inner electrode, sintering in an air atmosphere at a temperature of 1100°C and keeping warm for 3 hours to obtain a pulse power ceramic capacitor.

[0032] Dielectric material, with 100 mol parts of (Sr 0.7 Ba 0.27 Mg 0.03 )(Ti 0.8 Ru 0.15 Te 0.05 )O3 is used as the base material, and the following components are added in molar proportions: 7 parts of La3CeZr3O 12 , 1 part of Ba(Zn 1 / 6 Nb 1 / 3 )(B2O4)2, 0.7 parts of MnCO3, 0.35 parts of MnO2, 0.12 parts of Li2SiO3.

[0033] The preparation process comprises the following steps: Step 1: Preparation by molten salt method (Sr 0.7 Ba 0.27 Mg 0.03 )(Ti 0.8 Ru 0.15 Te 0.05 )O3: molar ratio of 0.7: 0.27: 0.03: 0.8: 0.15: 0.05: (2~4): (2~4) Weigh SrCO3, BaCO3, MgO, TiO2, RuO2, TeO2, NaCl, KCl respectively, add anhydrous ethanol and zirconium oxide beads, mix and ball mill for 6 hours, dry the powder and calcine it at 800~900℃ for 2.5 hours, and cool it naturally to room temperature; the calcined product is ultrasonically cleaned with deionized water, washed and filtered several times until there is no Cl - After washing and drying, (Sr 0.7 Ba 0.27 Mg 0.03 )(Ti 0.8 Ru 0.15 Te 0.05 )O3; Step 2: Preparation of La3CeZr3O by solid phase method 12 : La2O3, Ce2O3, and ZrO2 were weighed in a molar ratio of 1.5:0.5:3, deionized water and zirconium oxide beads were added, mixed and ball-milled for 5 hours, and the powder was dried and calcined at 1280°C for 2.5 hours, and naturally cooled to room temperature to obtain La3CeZr3O 12 ; Step 3: Solid phase method to prepare Ba(Zn 1 / 6 Nb 1 / 3 )(B2O4)2: BaCO3, ZnO, Nb2O5, B2O3 were weighed in a molar ratio of 1:1 / 6:1 / 6:3, and appropriate amount of deionized water and zirconium oxide beads were added and mixed and ball-milled for 5 hours. After drying, the powder was transferred to calcination at 720℃ for 2.5 hours and naturally cooled to room temperature to obtain Ba(Zn 1 / 6 Nb 1 / 3 )(B2O4)2; Step 4: (Sr 0.7 Ba 0.27 Mg 0.03 )(Ti 0.8 Ru 0.15 Te 0.05 )O3、La3CeZr3O 12 、Ba(Zn 1 / 6 Nb 1 / 3 )(B2O4)2, MnCO3, MnO2, Li2SiO3, add deionized water and zirconium oxide beads, ball mill for 6 hours and then dry and crush to obtain the dielectric material for the high dielectric constant pulse power ceramic capacitor.

[0034] Comparative Example 7 A high dielectric constant, high resistance and low loss pulse power ceramic capacitor is prepared using dielectric material. Its preparation process includes the following steps: subjecting the dielectric material to an MLCC process, using 70Ag-30Pd as an inner electrode, sintering in an air atmosphere at a temperature of 1100°C and keeping warm for 3 hours to obtain a pulse power ceramic capacitor.

[0035] Dielectric material, with 100 mol parts of (Sr 0.7 Ba 0.27 Mg 0.03 )(Ti 0.8 Ru 0.15 Te 0.05 )O3 as the base material, and the following components were added in molar proportions: 7 parts of La3(Sb 0.7 Ce 0.3 )Zr3O 12 , 1 part of Ba(Zn 1 / 6 Nb 1 / 3 )(B2O4)2, 0.7 parts of MnCO3, 0.35 parts of MnO2, 0.12 parts of Li2SiO3.

[0036] Step 1: Preparation by molten salt method (Sr 0.7 Ba 0.27 Mg 0.03 )(Ti 0.8 Ru 0.15Te 0.05 )O3: molar ratio of 0.7: 0.27: 0.03: 0.8: 0.15: 0.05: (2~4): (2~4) Weigh SrCO3, BaCO3, MgO, TiO2, RuO2, TeO2, NaCl, KCl respectively, add anhydrous ethanol and zirconium oxide beads, mix and ball mill for 6 hours, dry the powder and calcine it at 800~900℃ for 2.5 hours, and cool it naturally to room temperature; the calcined product is ultrasonically cleaned with deionized water, washed and filtered several times until there is no Cl - After washing and drying, (Sr 0.7 Ba 0.27 Mg 0.03 )(Ti 0.8 Ru 0.15 Te 0.05 )O3; Step 2: Solid phase method to prepare La3(Sb 0.7 Ce 0.3 )Zr3O 12 : La2O3, Sb2O3, Ce2O3, and ZrO2 were weighed in a molar ratio of 1.5:0.35:0.15:3, deionized water and zirconium oxide beads were added, mixed and ball-milled for 5 hours, and the powder was dried and calcined at 1280°C for 2.5 hours, and naturally cooled to room temperature to obtain La3(Sb 0.7 Ce 0.3 )Zr3O 12 ; Step 3: Solid phase method to prepare Ba(Zn 1 / 6 Nb 1 / 3 )(B2O4)2: BaCO3, ZnO, Nb2O5, B2O3 were weighed in a molar ratio of 1:1 / 6:1 / 6:3, and appropriate amount of deionized water and zirconium oxide beads were added and mixed and ball-milled for 5 hours. After drying, the powder was transferred to calcination at 720℃ for 2.5 hours and naturally cooled to room temperature to obtain Ba(Zn 1 / 6 Nb 1 / 3 )(B2O4)2; Step 4: (Sr 0.7 Ba 0.27 Mg 0.03 )(Ti 0.8 Ru 0.15 Te 0.05 )O3、La3(Sb 0.7 Ce 0.3 )Zr3O 12 、Ba(Zn 1 / 6 Nb 1 / 3)(B2O4)2, MnCO3, MnO2, Li2SiO3, add deionized water and zirconium oxide beads, ball mill for 6 hours and then dry and crush to obtain the dielectric material for the high dielectric constant pulse power ceramic capacitor.

[0037] Comparative Example 8 A high dielectric constant, high resistance and low loss pulse power ceramic capacitor is prepared using dielectric material. Its preparation process includes the following steps: subjecting the dielectric material to an MLCC process, using 70Ag-30Pd as an inner electrode, sintering in an air atmosphere at a temperature of 1100°C and keeping warm for 3 hours to obtain a pulse power ceramic capacitor.

[0038] Dielectric material, with 100 mol parts of (Sr 0.7 Ba 0.27 Mg 0.03 )(Ti 0.8 Ru 0.15 Te 0.05 )O3 as the base material, and the following components were added in molar proportions: 7 parts of La3(Sb 0.3 Ce 0.7 )Zr3O 12 , 1 part of Ba(Zn 1 / 6 Nb 1 / 3 )(B2O4)2, 0.7 parts of MnCO3, 0.35 parts of MnO2, 0.12 parts of Li2SiO3.

[0039] The preparation process comprises the following steps: Step 1: Preparation by molten salt method (Sr 0.7 Ba 0.27 Mg 0.03 )(Ti 0.8 Ru 0.15 Te 0.05 )O3: molar ratio of 0.7: 0.27: 0.03: 0.8: 0.15: 0.05: (2~4): (2~4) Weigh SrCO3, BaCO3, MgO, TiO2, RuO2, TeO2, NaCl, KCl respectively, add anhydrous ethanol and zirconium oxide beads, mix and ball mill for 6 hours, dry the powder and calcine it at 800~900℃ for 2.5 hours, and cool it naturally to room temperature; the calcined product is ultrasonically cleaned with deionized water, washed and filtered several times until there is no Cl - After washing and drying, (Sr 0.7 Ba 0.27 Mg 0.03 )(Ti 0.8 Ru 0.15 Te 0.05 )O3; Step 2: Solid phase method to prepare La3(Sb0.3 Ce 0.7 )Zr3O 12 : La2O3, Sb2O3, Ce2O3, and ZrO2 were weighed in a molar ratio of 1.5:0.15:0.35:3, deionized water and zirconium oxide beads were added, mixed and ball-milled for 5 hours, and the powder was dried and calcined at 1280°C for 2.5 hours, and naturally cooled to room temperature to obtain La3(Sb 0.3 Ce 0.7 )Zr3O 12 ; Step 3: Solid phase method to prepare Ba(Zn 1 / 6 Nb 1 / 3 )(B2O4)2: BaCO3, ZnO, Nb2O5, B2O3 were weighed in a molar ratio of 1:1 / 6:1 / 6:3, and appropriate amount of deionized water and zirconium oxide beads were added and mixed and ball-milled for 5 hours. After drying, the powder was transferred to calcination at 720℃ for 2.5 hours and naturally cooled to room temperature to obtain Ba(Zn 1 / 6 Nb 1 / 3 )(B2O4)2; Step 4: (Sr 0.7 Ba 0.27 Mg 0.03 )(Ti 0.8 Ru 0.15 Te 0.05 )O3、La3(Sb 0.3 Ce 0.7 )Zr3O 12 、Ba(Zn 1 / 6 Nb 1 / 3 )(B2O4)2, MnCO3, MnO2, Li2SiO3, add deionized water and zirconium oxide beads, ball mill for 6 hours and then dry and crush to obtain the dielectric material for the high dielectric constant pulse power ceramic capacitor.

[0040] Comparative Example 9 A high dielectric constant, high resistance and low loss pulse power ceramic capacitor is prepared using dielectric material. Its preparation process includes the following steps: subjecting the dielectric material to an MLCC process, using 70Ag-30Pd as an inner electrode, sintering in an air atmosphere at a temperature of 1100°C and keeping warm for 3 hours to obtain a pulse power ceramic capacitor.

[0041] Dielectric material, with 100 mol parts of (Sr 0.7 Ba 0.27 Mg 0.03 )(Ti 0.8 Ru 0.15 Te 0.05 )O3 as the base material, and the following components were added in molar proportions: 7 parts of La3(Sb0.87 Ce 0.13 )Zr3O 12 , 1 part of BaZnB2O4, 0.33 parts of Nb2O5, 0.7 parts of MnCO3, 0.35 parts of MnO2, and 0.12 parts of Li2SiO3.

[0042] The preparation process comprises the following steps: Step 1: Preparation by molten salt method (Sr 0.7 Ba 0.27 Mg 0.03 )(Ti 0.8 Ru 0.15 Te 0.05 )O3: molar ratio of 0.7: 0.27: 0.03: 0.8: 0.15: 0.05: (2~4): (2~4) Weigh SrCO3, BaCO3, MgO, TiO2, RuO2, TeO2, NaCl, KCl respectively, add anhydrous ethanol and zirconium oxide beads, mix and ball mill for 6 hours, dry the powder and calcine it at 800~900℃ for 2.5 hours, and cool it naturally to room temperature; the calcined product is ultrasonically cleaned with deionized water, washed and filtered several times until there is no Cl - After washing and drying, (Sr 0.7 Ba 0.27 Mg 0.03 )(Ti 0.8 Ru 0.15 Te 0.05 )O3; Step 2: Solid phase method to prepare La3(Sb 0.87 Ce 0.13 )Zr3O 12 : La2O3, Sb2O3, Ce2O3, and ZrO2 were weighed in a molar ratio of 1.5:0.435:0.065:3, deionized water and zirconium oxide beads were added, mixed and ball-milled for 5 hours, and the powder was dried and calcined at 1280°C for 2.5 hours, and naturally cooled to room temperature to obtain La3(Sb 0.87 Ce 0.13 )Zr3O 12 ; Step 3: Prepare BaZnB2O4 by solid phase method: weigh BaCO3, ZnO and B2O3 in a molar ratio of 1:1:2 respectively, add appropriate amount of deionized water and zirconium oxide beads, mix and ball mill for 5 hours, and after drying, transfer the powder to calcine at 720°C for 2.5 hours, and cool naturally to room temperature to obtain BaZnB2O4; Step 4: (Sr 0.7 Ba 0.27 Mg 0.03 )(Ti 0.8 Ru0.15 Te 0.05 )O3、La3(Sb 0.87 Ce 0.13 )Zr3O 12 , BaZnB2O4, Nb2O5, MnCO3, MnO2, Li2SiO3, add deionized water and zirconia beads, ball mill for 6 hours and then dry and crush to obtain the dielectric material for the high dielectric constant pulse power ceramic capacitor.

[0043] The pulse power ceramic capacitors prepared in Examples 1-5 and Comparative Examples 1-7 were tested to obtain the following data, as shown in Table 2.

[0044] Table 2 Performance test table

[0045] Where, K: dielectric constant; TCC: temperature coefficient of capacitance; IR: insulation resistance; DF: loss tangent.

[0046] It can be seen from the above table that the present application provides Examples 1 to 5, and by adjusting the content of each component, pulse power ceramic dielectric materials with good performance can be obtained; among them, the pulse power ceramic capacitor prepared in Example 1 can provide a higher dielectric constant ( K = 632), relatively stable capacitance temperature coefficient (-2100±200 ppm / K ), the highest breakdown electric field (>49.43 V / μm ), the highest insulation resistance: 14980 MΩ ; and excellent discharge current (>1800 A ).

[0047] By comparing Example 1 with Comparative Example 1, it can be seen that La3(Sb 0.87 Ce 0.13 )Zr3O 12 Not only maintain (Sr 0.7 Ba 0.27 Mg 0.03 )(Ti 0.8 Ru 0.15 Te 0.05 )O3 high K The addition of important doping materials and the fusion of the two materials can significantly improve the breakdown electric field and discharge current of the material.

[0048] By comparing Example 1 with Comparative Example 2, it can be seen that without the sintering aid Ba(Zn 1 / 6 Nb 1 / 3)(B2O4)2, the electrical properties of the ceramic body deteriorated rapidly after firing, the K value decreased to 376, the TCC increased significantly, the breakdown electric field decreased to 33.24 V / μm, and the loss increased to 32.9×10 -4 , the discharge current is reduced to 1223 A; by comparing Example 1 with Comparative Example 9, if Nb2O5 is added to the material alone, a lower dielectric loss can be obtained: 2.2×10 -4 However, the other electrical properties are significantly reduced. Therefore, the appropriate amount of sintering aid plays an important role in the sintering process of ceramic materials.

[0049] By comparing Example 1 with Comparative Examples 3-4, it can be seen that Mn 2+ / Mn 4+ The ratio of Mn 2+ / Mn 4+ =2:1 can play a better role in improving the discharge current of the material, Mn 2+ / Mn 4+ Too high or too low a ratio is not conducive to improving the polarization strength of the material. P m .

[0050] By comparing Example 1 with Comparative Example 5, it can be seen that adding a trace amount of Li element can further improve the energy storage density of the material, which is measured in the form of an increase in discharge current.

[0051] By comparing Example 1 with Comparative Examples 6-8, it can be seen that if La3(Sb 0.87 Ce 0.13 )Zr3O 12 The ratio of Sb / Ce in the dielectric material is too high or too low. The high stability of La and Ce cannot be fully exerted. The Sb / Ce ratio needs to be limited to 0.87 / 0.13 in Example 1, so that the dielectric material can obtain the best electrical performance. In summary, the pulse power ceramic dielectric material proposed in the present invention is made by adding Ru and Te elements during the process of making the main substrate to make (Sr 0.7 Ba x Mg 0.3-x )(Ti 0.8 Ru y Te 0.2-y )O3, and then La3(Sb z Ce 1-z )Zr3O 12 , synthesized improved sintering aid Ba(Zn 1 / 6 Nb 1 / 3 )(B2O4)2, and by adjusting the Mn 2+ / Mn 4+The ratio of the polarization intensity is higher P m In the presence of trace amounts of Li elements, the dielectric material obtained has excellent electrical properties of high dielectric constant, high resistance and low loss. The capacitor made of this dielectric material has excellent bias characteristics, stable charge and discharge performance and large discharge current, and is suitable for use as a pulse power ceramic capacitor.

Claims

1. A dielectric material for a high dielectric constant, high resistance, low loss power capacitor, characterized in that: With 100 mol parts of (Sr 0.7 Ba x Mg 0.3-x )(Ti 0.8 Ru y Te 0.2-y )O3 as the base material, and the following components are added in molar proportions: 2 to 10 parts of La3(Sb z Ce 1-z )Zr3O 12 , 1~3 parts of Ba(Zn 1 / 6 Nb 1 / 3 )(B2O4)2, 0.5~1 parts of MnCO3, 0.2~0.5 parts of MnO2, 0.1~0.2 parts of Li2SiO3, wherein 0<x<0.3, 0.1<y<0.2, 0.7<z<1.

0.

2. The dielectric material for high dielectric constant, high resistance and low loss power capacitor according to claim 1, characterized in that: The Ba(Zn 1 / 6 Nb 1 / 3 )(B2O4)2 is synthesized from BaCO3, ZnO, Nb2O5 and B2O3 using a fixed method.

3. The dielectric material for a high dielectric constant, high resistance, low loss power capacitor according to claim 1, characterized in that: The (Sr 0.7 Ba x Mg 0.3-x )(Ti 0.8 Ru y Te 0.2-y )O3 is (Sr 0.7 Ba 0.27 Mg 0.03 )(Ti 0.8 Ru 0.15 Te 0.05 )O3.

4. The dielectric material for high dielectric constant, high resistance and low loss power capacitor according to claim 1, characterized in that: The La3(Sb z Ce 1-z )Zr3O 12 La3(Sb 0.87 Ce 0.13 )Zr3O 12 .

5. The process for preparing a dielectric material for a high dielectric constant, high resistance and low loss power capacitor according to claim 1, characterized in that: The following steps are involved: Step 1: Preparation by molten salt method (Sr 0.7 Ba x Mg 0.3-x )(Ti 0.8 Ru y Te 0.2-y )O3; Step 2: Solid phase method to prepare La3(Sb z Ce 1-z )Zr3O 12 ; Step 3: Solid phase method to prepare Ba(Zn 1 / 6 Nb 1 / 3 )(B2O4)2; Step 4: (Sr 0.7 Ba x Mg 0.3-x )(Ti 0.8 Ru y Te 0.2-y )O3、La3(Sb z Ce 1-z )Zr3O 12 、MnCO3、MnO2、Ba(Zn 1 / 6 Nb 1 / 3 )(B2O4)2, Li2SiO3, add deionized water and zirconium oxide beads, ball mill for 4 to 6 hours, then dry and crush to obtain the dielectric material for high dielectric constant, high resistance and low loss pulse power ceramic capacitor.

6. The process for preparing a dielectric material for a high dielectric constant, high resistance, low loss power capacitor according to claim 5, characterized in that: Step 1 specifically comprises: weighing SrCO3, BaCO3, MgO, TiO2, RuO2, TeO2, NaCl, and KCl respectively in a molar ratio of 0.7:x:(0.3-x):0.8:y:(0.2-y):(2~4):(2~4), adding anhydrous ethanol and zirconium oxide beads, mixing and ball milling for 6~8h, drying and calcining the powder at a temperature of 800~900℃ for 2-3h, and naturally cooling to room temperature; the calcined product is ultrasonically cleaned with deionized water, washed and filtered for multiple times until there is no Cl - After washing and drying, (Sr 0.7 Ba x Mg 0.3-x )(Ti 0.8 Ru y Te 0.2-y )O3.

7. The process for preparing a dielectric material for a high dielectric constant, high resistance, low loss power capacitor according to claim 5, characterized in that: Step 2 specifically includes: La3(Sb z Ce 1-z )Zr3O 12 The specific preparation process is as follows: La2O3, Sb2O3, Ce2O3, and ZrO2 are weighed separately in a molar ratio of 1.5:z / 2:(1-z) / 2:3, deionized water and zirconium oxide beads are added, mixed and ball-milled for 4-6 hours, and the powder is dried and calcined at 1200-1300°C for 1-3 hours, and naturally cooled to room temperature to obtain La3(Sb z Ce 1-z )Zr3O 12 .

8. The process for preparing a dielectric material for a high dielectric constant, high resistance, low loss power capacitor according to claim 5, characterized in that: Step 3 specifically includes: Ba(Zn 1 / 6 Nb 1 / 3 The specific preparation process of )(B2O4)2 is as follows: BaCO3, ZnO, Nb2O5, and B2O3 are weighed in a molar ratio of 1:1 / 6:1 / 6:3, and appropriate amounts of deionized water and zirconium oxide beads are added and mixed and ball-milled for 4-6 hours. After drying, the powder is transferred to a temperature of 600-800°C and calcined for 1-3 hours, and naturally cooled to room temperature to obtain Ba(Zn 1 / 6Nb 1 / 3 )(B2O4)2.

9. A high dielectric constant, high resistance, low loss power capacitor, characterized in that: The dielectric material according to claim 1 is used for preparation.

10. The process for preparing a high dielectric constant, high resistance and low loss power capacitor according to claim 9, characterized in that: The following steps are involved: The dielectric material is subjected to an MLCC process, with 70Ag-30Pd as the inner electrode, sintered in an air atmosphere at a temperature of 1000-1200° C., and kept warm for 2-5 hours to obtain the pulse power capacitor.

Citation Information

Patent Citations

  • Pulse power capacitor ceramic material with high breakdown strength and method for preparing pulse power capacitor ceramic material

    CN108530059A

  • Ceramic pulse capacitor and dielectric material, and preparation methods thereof

    CN113248251A

  • Pulse power type ceramic dielectric material, pulse power type ceramic capacitor and preparation method thereof

    CN116425527A

  • High-dielectric-constant pulse power type ceramic capacitor, dielectric material for high-dielectric-constant pulse power type ceramic capacitor and preparation method of dielectric material

    CN117577448A